The Prothrombin 20210A Allele and Its Association with Myocardial Infarction - Croft, S. A.; Daly, M. E.; Steeds, R. P.; Channer, K. S.; Samani, N. J.; Hampton, K. K. (Thrombosis and Haemostasis, 1999)
The relationship between the prothrombin (PT) 20210A allele and arterial disease is controversial. We conducted a case-control study to assess its contribution to risk of myocardial infarction (MI). Five hundred and thirty-nine acute MI patients and 498 control subjects aged <75 years were studied. Two percent of cases carried the PT20210A allele compared to 2.8% of controls. The odds ratio for MI was 0.72 (95% CI 0.32-1.60) indicating that the PT20210A allele confers no increased risk for MI. Subgroup analysis showed no association between the PT20210A allele and either premature MI or MI in females. We conclude the PT20210A allele is not a risk factor for MI and suggest that discrepancies in studies relating the PT20210A allele to MI may be due to difficulties in estimating its low allelic frequency in the general population and thus random differences in the observed frequencies in the control populations studied.